Pewarisan Pengetahuan Etnobotani Minyak Rempah dalam Terapi Pijat Tunanetra Suharno - Febrianto, Alfilliano; Wicaksono, Harto (Program Studi Sosiologi Universitas Malikussaleh, 2023)
The ethnobotanical knowledge of Minyak Rempah provides an important perspective on the relationship between plants and culture. Minyak Rempah is used as a medicine in the practice of Suharno's blind massage therapy experiencing the inheritance of knowledge that exists until now. This study aims to describe the process of inheritance of ethnobotanical knowledge in Suharno blind massage therapy treatment practice in Kemadohan, Ngalas Village, South Klaten District, Klaten Regency. The data was obtained using qualitative methods. The data collection techniques used were participatory observation and informant interviews. The results showed that there was a combination of plants and liquid paraffin used to make Minyak Rempah. The ethnobotanical knowledge of Minyak Rempah in Suharno blind massage therapy is inherited through a cultural learning process which is divided into three stages, namely intenalization, socialization, and enculturation. The learning process is based on Ilmu Kedaton which explains the knowledge that three types of diseases can be treated with Minyak Rempah and massage therapy. The success of the learning process of ethnobotanical knowledge of Minyak Rempah and massage therapy is indicated by the knowledge being made part of daily life as a local medicine practitioner.Pengetahuan etnobotani Minyak Rempah memberikan perspektif penting hubungan antara tumbuhan dan budaya. Minyak Rempah digunakan sebagai obat pada praktik terapi pijat tunantetra Suharno mengalami pewarisan pengetahuan yang bertahan hingga saat ini. Kajian ini bertujuan untuk menganalisis proses pewarisan pengetahuan etnobotani pada praktik pengobatan terapi pijat tunanetra Suharno di Dukuh Kemadohan, Desa Ngalas, Kecamatan Klaten Selatan, Kabupaten Klaten. Data diperoleh menggunakan metode kualitatif. Teknik pengumpulan data yang digunakan adalah observasi partisipatoris dan wawancara informan. Hasil penelitian menunjukan terdapat kombinasi tumbuhan dan parafin cair yang digunakan untuk pembuatan Minyak Rempah. Pengetahuan etnobotani Minyak Rempah dalam terapi pijat tunanertra Suharno diwariskan melalui proses belajar kebudayaan yang terbagi menjadi tiga tahap yaitu intenalisasi, sosialisasi, dan enkulturasi. Proses belajar didasarkan pada Ilmu Kedaton yang menjelaskan pengetahuan tiga jenis penyakit dapat diobati dengan Minyak Rempah dan terapi pijat. Keberhasilan proses belajar pengetahuan etnobotani Minyak Rempah dan terapi pijat ditandai dengan pengetahuan tersebut dijadikan bagian dari kehidupan sehari-hari sebagai praktisi pengobatan lokal.